13C NMR investigations of molecular order of rod‐like, bent‐core, and thiophene mesogens. (21st December 2019) - Lobo, Nitin P.; Ramanathan, K.V.; Narasimhaswamy, T.
Abstract: In this review, methods to obtain the orientational order of topologically variant molecular mesogens using by one‐ and two‐dimensional (2D) solid‐state 13 C nuclear magnetic resonance (NMR) spectroscopy are described. Besides 13 C chemical shifts, the 13 C─ 1 H dipolar couplings measured from 2D‐separated local field (SLF) technique are used for computing the order parameters of a variety of mesogens. The investigated molecules are composed of a variable number of rings in the core, that is, core ranging from simply one ring to five rings. Among the mesogens investigated, a special focus has been placed on mesogens with thiophene rings, which are gaining popularity as liquid crystalline organic semiconductors. The replacement of a phenyl ring by thiophene in the core has a dramatic influence on molecular topology, as observed from the measured order parameters. The review highlights the advantages of the 2D SLF method for understanding the local dynamics and for mapping the topology of mesogens through the measured order parameters. SLF NMR studies of as many as 24 molecular mesogens that vary in terms of the molecular structure as well as topology are covered in the review. Order parameters of the rings have been estimated from the 13 C─ 1 H dipolar couplings in the nematic, smectic A, smectic C, and tilted hexatic phases as well as in B1 and B2 mesophases of various mesogens. It is anticipated that, in the years to come, the 2D SLF method would provide advanced molecular information on structurally complex mesogens that are emerging in liquid crystal science through the incessant efforts of synthetic chemists. The mini review covers the orientational order of topologically variant molecular mesogens determined by 1D and 2D solid‐state 13 C NMR spectroscopy. Accordingly, rod‐like, bent‐core, and thiophene mesogens were subjected to 2D SLF measurements to get the order parameters from which the topology was established. The replacement of phenyl ring by thiophene and its influence on order parameters as well as on molecular topology is also discussed.